Potential Benefits of Allogeneic Haploidentical Adipose Tissue-Derived Stromal Vascular Fraction in a Hutchinson–Gilford Progeria Syndrome Patient - Pak, Jaewoo; Lee, Jung Hun; Jeon, Jeong Ho; Kim, Young Bae; Jeong, Byeong Chul; Lee, Sang Hee (Frontiers in Bioengineering and Biotechnology, 2020)
Hutchinson-Gilford Progeria Syndrome (HGPS) is a rare, fatal, and genetic disorder in the LMNA gene encoding for prelamin A. Normally, prelamin A is processed to become lamin A protein. In HGPS patients, there is a heterozygous mutation in LMNA gene, in which there is a deletion of genetic codes responsible for 50 amino acids at the C-terminus of prelamin A. The processing of the abnormal prelamin A results in abnormal lamin A protein, called progerin, causing symptoms of accelerated early aging, probably due to the inflammaging process. It is well known that adipose tissue-derived mesenchymal stem cells (MSCs) have anti-inflammatory effects by modulating inflammatory cytokines and by extracellular vesicles. Here, we present a case of an HGPS patient who responded positively to injections of allogeneic haploidentical adipose tissue-derived stromal vascular fractions containing MSCs by showing rapid height and weight growth along with increased blood level of insulin-like growth factor-1.